Book Reviews - Irving , Baiba; Jennings , Margaret (Archives & Manuscripts, 1978)
J. Reed and K. Oakes. Women in Australian society, 1901-1943 reviewed by Baiba Irving; K. Daniels, M. Murnane, A. Picot. Women in Australia reviewed by Margaret Jennings